Molecular structural differences between maize leaf and endosperm starches. (1st April 2017) - Yu, Shiyao; Zhang, Fangdong; Li, Cheng; Gilbert, Robert G.
Highlights: Leaf starch has much shorter amylopectin chains than endosperm starch. Leaf starch has much smaller molecules than endosperm starch. Leaf starch granules are smaller than endosperm granules. Differences between leaf and endosperm starch related to their biosynthesis process. Abstract: The morphology, whole molecular size distribution and chain-length distribution of maize leaf starch have been characterized and compared to its endosperm starch, to better understand differences between leaf and endosperm starch structure, and the relationship with the functions of starch in these organs. Leaf starch is found to have amylopectin with much shorter chains (virtually none with a degree of polymerization, DP, above 70) than the endosperm amylopectin, which has significant numbers of chains with DP up to ∼120, and has much smaller molecular size (and is present at a much lower amount) than endosperm starch. It is postulated that these pronounced differences arise from the distinct starch synthesis pathways in these organs, and are consistent with the starches' distinct botanical functions: short-term storage requiring relatively rapid degradation for leaf starch, and high crystallinity and high energy density requiring slow degradation for endosperm starch.